ANALISIS PROSES PRODUKSI PADA USAHA KECIL DAN MENENGAH (UKM) TAHU DI KELURAHAN JOMBLANG BERBASIS EKO-EFISIENSI (STUDI PADA UKM TAHU HARAPAN TENANG SEMARANG) - Agtriani, Nadia Nur; Prabawani, Bulan (Departemen Administrasi Bisnis, FISIP Universitas Diponegoro, 2020)
Eco-Efficiency is a concept of efficiency by minimizing the use of raw materials, water, and energy, as well as their impact on the environment. This thing can reduce the percentage of NPO costs to total production costs.This study aims to determine the implementation of eco-efficiency in Small and Medium Enterprise (SME) Tahu Harapan Tenang of Semarang. The type of research used is a case study. Analysis of the model uses descriptive analytical with a qualitative approach. Data collection, uses interviews, observations, data collection and literature studies SME Tahu Harapan Tenang is a small scale industry that still operates traditionally with eight workers that can produce 500kg of soy every day. This production produces waste that damages the environment. The purpose of this eco-efficiency analysis is to minimize the use of raw materials, energy, water, and non-product output in each product unit. Based on the results of the analysis of production in a day, the NPO (NonProduct Output) in the boiling water process was Rp2,274.28; NPO in the soybean immersion process was Rp638.26; NPO in the washing soybeans process was Rp495,528.22; NPO in the soybean milling process was Rp33,748.31; NPO in the boiling process was Rp528.22; NPO in the screening process was Rp330,528.22; NPO in the deposition process was Rp528.22; NPO in the tofu printing process was Rp528.22; NPO in the tofu cutting process was Rp528.22; NPO in the tofu immersion process was Rp3,647.73; NPO in tofu frying process was Rp69,037.69; NPO in the process of selecting and counting fried tofu was Rp237.69. Thus, the total NPO cost is Rp937,753.28 Researcher suggests the SME Tahu Harapan Tenang record costs during production precisely and accurately. The recording is done to obtain the minimum disposal of raw materials, energy, and water, and produce the lowest NPO cost.